Interpreter Training in the Republic of Ireland: An Overview - Hoyte-West, Antony (Verbum, 2020)
Although the Republic of Ireland is a bilingual country,this study illustrates that there are comparatively few domestic training options available for interpreters of spoken languages. In providing an overview of the present state of affairs, this article contextualises the current linguistic situation both within the country and at the European level. Attention is paid to the recognition of Irish as an official language of the European Union (EU), as well as tothe corresponding implications for interpreter training. In addition, the domestic situation regarding community interpreters is also outlined, with the lack of official regulation of the interpreting profession also noted. Subsequently, the options for interpreter training in tertiary education are outlined, both at the undergraduate and the postgraduate level. In addition, relevant information regarding the structure and content of the modules and courses is provided. To conclude, some thoughts regarding potential developments of interpreter training in the Irish context are outlined.